The Outcome Of Retaining A Stable Implant In Ununited Infected Fracture Following Open Reduction And Internal Fixation Of Closed Fractures In Long Bones - Mohd Yusof, Nazri (2001)
This is a retrospective study of 30 patients with ununited infected fractures but with stable implant. The study was done between January 1995 to December 2000 in University Science Malaysia Kubang Kerian. An infected ununited fracture is an orthopedic dilemma in deciding whether to remove the implant or retain it until union has been achieved. The aim of this study is to determine the outcome of patients where the stable implants were retained despite the presence of infection. This study is also aimed to identify the risk factors for failure of treatment and identify the microbiology pattern. The result of this study showed a success rate of 77% • The commonest organism was Staphylococcus aureus which had been identified in 800/0 of patients. This stUdy showed that site and severity of fracture, type of implant, onset and severity of infection , type of organism and associated medical problems and injuries does not significantly influence the outcome of patient with an infected ununited fractures of long bone with retained internal fixation. I concluded that retaining an infected but stable implant in ununited fracture until the fractur~ has healed can be an initial treatment for all patients with infected fractures following open reduction and internal fixation of closed fractures in long bones.